Nursing Interventions to Improve Self-management in Patients with Type 2 Diabetes Mellitus: A Scoping Review - Fitriani,; Agus, Al Ihksan (Africa Journal of Nursing and Midwifery, 2024)
Background: Type 2 diabetes mellitus (T2DM) is a chronic disease that remains a public health problem both in developed and developing countries. As the prevalence of diabetes mellitus increases, nurses can take part in managing this disease so that health outcomes can also be improved. Strategies for sustaining diabetes self-management are, therefore, pivotal. Objective: This review aimed to identify existing evidence regarding interventions performed by nurses in enhancing self-management of patients with T2DM. Methods: This study was a scoping review with T2DM adults as the population of interest. The literature search was conducted in May 2023 using PubMed, CINAHL, and Medline as the resource databases. The study selection followed PRISMA guidelines. The keywords were “nursing interventions,” “type 2 diabetes mellitus,” and “self-management.” Results: A total of 22 studies were included for review, including 10 RCT studies, one quasi-experimental study, two qualitative studies, one systematic review, one qualitative systematic review, and seven meta-analyses. The studies were undertaken in Australia, the United States of America, Norway, Spain, Turkey, South Korea, China, Singapore, Ethiopia, Taiwan, and Iran. Of those studies, 10 discussed technology-based intervention, five reported a nurse-led education approach, two reported a patient-centred self-management approach, one reported motivational interviewing, two discussed an empowerment-based approach, one reported psychological intervention, two reported a case management programme, and one reported structured as well as individualised education approaches. Conclusion: Various nursing interventions can be implemented to improve self-management of T2DM patients. This review can inform nurses regarding intervention options applicable to their workplace conditions.